Structure and use of idiomatic expressions in written Nigerian English - Muhammad, Umar Aliyu (2016)
There are idioms in Nigerian English which came about as a result of both cultural and linguistic influences of the users of English in Nigeria. A greater portion of the research conducted in English idioms are either on native speakers use and acquisition; or on non-native speakers use and acquisition of idioms in Standard English; but not on non-native speakers use and acquisition of idioms in non native varieties of English. In fact even studies Nigerian English have tended to discuss the variety holistically without any particular attention to idioms. Moreover, the existing corpora and idiom dictionaries of English do not feature idioms from L2 varieties of English. This research work is a modest attempt to address this dearth of research. The main aim is to identify, from a corpus of written materials, idioms in context in the variety of English in use in Nigeria with a view to understanding their unique structure/use and the contribution of indigenous languages to this. The word sense disambiguation (WSD) by Hashimoto and Kawahara (2009) was adapted and used to identify idioms in sixty issues from two major newspaper titles in Nigeria – the Daily Trust and the Vanguard. This source base was augmented by other sources like novels and articles written about idioms. A total of 2,212 idiom samples were identified. This number was converted to 1,415 idiom tokens by removing repetitions and conjugations. To isolate the idioms unique to Nigerian English the tokens were checked in five English idiom dictionaries and two web corpora. After this checking it was concluded that the use and structure of 174 idioms were unique to Nigerian English. With accommodation theory and Muysken’s Quadrangled model providing the theoretical basis, the analysis of the result shows that the indigenous languages have contributed in shaping both the structure and use of idioms in Nigerian English. The usage pattern which shows that more idioms are used in the south of Nigeria than in the north can be explained by the accommodation principles of convergence, divergence and maintenance. The unique structure of some idioms can be explained by Muysken’s quadrangled model of languages in contact. There are idioms that can be found across most varieties of English, there are also idioms that have been modified from their original forms as a result of the Nigerian linguistic environment. All these point to a vibrant and interesting circumstance in which much more insight can be gained in the study of Nigerian English. This research work shows that there are actually idioms unique to Nigerian English and their number is substantial enough to warrant the publication of a dictionary of idioms in Nigerian English. The compilation of a corpus for Nigerian English is thus feasible especially with an expanded data base.